Misselling jako nadużywanie zaufania klienta na rynku finansowym - Paduszyńska, Marta (Annales. Etyka w Życiu Gospodarczym, 2019)
The amendment to the act on competition and consumer protection, in force since 17 April 2016, introduced a ban on the so-called ‘misselling’ as a new type of practice that violates collective consumer interests. The sale of products that are not suited to the needs of clients is a frequent reason for complaints to courts and institutions of consumer protection. Thus, it has a negative impact on clients' trust in financial market entities, because it exposes them to unnecessary risk and generates additional service costs. The financial services market is a type of market that has a significant impact on its customers. The source of threats may be the fact that financial institutions operate in an area of increased risk with a relatively low share of equity, and also, they rely on the funds entrusted to them by clients. The aim of this paper is to identify the phenomenon of misselling, explain the reasons for which it is undesirable from the point of view of consumer protection, and present solutions for its reduction. The paper is based on a review, analysis, and synthesis of selected publications (domestic and foreign) which are important from the point of view of the topic. Moreover, the paper includes an analysis of secondary data from official documents and reports of financial market entities.